Research on orbital angular momentum communication technology - Feng ZHENG; Yijian CHEN; Siwei JI; Gaoming DUAN; Guanghui YU (Tongxin xuebao)
As the good orthogonality between the different modes of orbital angular momentum (OAM),the application of OAM technology in wireless communication has gained increasing popularity in recent years with great potential for capacity improvement.OAM-based wireless communication technology can effectively improve spectrum utilization,but also brings some challenges.Firstly,the research status and progress of OAM technology in the field of wireless communication were introduced and the relationship between OAM and MIMO technology was compared and analyzed combined with the basic principle of OAM.Moreover,the dispute “Does OAM provides a new dimension?” was concluded.Then,the generation and reception methods of OAM were summarized.The key techniques and application fields were overviewed.Finally,the challenges of the technology in practical application were analyzed and the future development trends and follow-up research directions were point out,which would provide a reference and help for the research in this field.